Pengembangan Instrumen Tes Diagnostik Dengan Certainty Of Response Index Untuk Mengidentifikasi Miskonsepsi Siswa Pada Materi Ikatan Kimia - Ebiati Ebiati (Journal Evaluation in Education (JEE), 2021)
Research objectives: This study aims to find out misconceptions through a diagnostic test using the Certainty of Response Index method. Methodology: This method can describe the respondent's belief in the truth of the alternative answers that are responded to based on the instructions in working on the questions. This study aims to develop a diagnostic test instrument with a certainty of response index to identify high school students' misconceptions on chemical bonding material and conduct tests to determine students' perceptions of the instrument. The diagnostic test instrument made, which only includes feasibility testing based on expert validation and student responses, is not tested to identify students' misconceptions. This study uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluations). The data analysis technique used in this research is qualitative data analysis and quantitative data analysis. Main findings: The developed diagnostic test instrument was validated by material experts in two stages with the percentage of eligibility of 87.78% and 92.2%, respectively. Media validation was carried out in three stages with the percentage of eligibility for stage I 80%, stage II 93.3%, and stage III with a percentage of 100%. For each stage of media validation based on the eligibility criteria, it is in the 81%-100% interval with the "very feasible" criteria to be tested. Novelty of research: Based on the data obtained in a large group trial at SMAN 1 Jambi City, students' perceptions of the diagnostic test instrument to identify students' misconceptions on chemical bonding material are in the "very feasible" category.